Prioritization of sub watersheds of a river basin using geographic information system - ATHULYA C SAJIRA A. K; Dr. Sathian K. K (Guide) (Tavanur 2012 Department of Land and Water Resources and Conservation Engineering)
Prioritization of sub watersheds of a river basin using geographic information system
Prioritization of sub watersheds of a river basin using geographic information system